Improving the Quality of Public Services from an Indonesian Village Perspective - Utami, Fitria Rochma; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2024)
This qualitative study examines the quality of population administration services in Bluru Kidul Village, Indonesia, aligning with the government's mandate to provide essential services as per Law Number 25 of 2009. Through interviews, observations, and document analysis, the research evaluates service quality dimensions including tangibles, reliability, responsiveness, assurance, and empathy. Findings indicate a favorable service environment, prompt and accurate service provision, swift handling of requests, caring employee attitudes, and friendly, non-discriminatory treatment of service users. These insights offer valuable guidance for policymakers and administrators to enhance service quality, thereby fostering greater citizen satisfaction and trust in government institutions. Highlights: Thorough assessment of population service quality. Adherence to Indonesia's governmental mandate. Priority on citizen satisfaction and trust. Keywords: Population administration services, Service quality assessment, Government mandate, Indonesia, Citizen satisfaction.